An integrated mHealth campaign to reduce the risk of falling for older adults - Brew-Sam, Nicola (2023)
The number of falls among older adults is rising due to an aging population worldwide. An integrated communication campaign utilizing mHealth (mobile health) encouraged older adults to perform strength, balance, and flexibility exercises to reduce their risk of falling. Campaign development was guided by a mixed-method approach which incorporated expert interviews (N = 3), qualitative interviews (N = 22), and a quantitative baseline pre-campaign survey (N = 274) with older adults. We evaluated the campaign impact with a pre-post survey analysis (post n = 141). Impact was measured by knowledge, attitudes, self-efficacy, and behaviors as key Social Cognitive Theory factors to exercise adoption. Results showed that respondents with campaign exposure had a significant increase in all factor scores from pre- to post-campaign survey, which was significantly higher in the group with campaign exposure. The impact evaluation illustrated how digital mobile channels effectively provide means to reach older adults to reduce their risk of falling.